EXPLORING THE IMPACT OF ARTIFICIAL INTELLIGENCE ON FOREIGN LANGUAGE ANXIETY IN LANGUAGE LEARNING (INDONESIA AND ENGLISH) - Aly, Abdul Hamid; Didah Nurhamidah (LPPM Universitas Nias Raya, 2025)
This study explores the impact of Artificial Intelligence (AI) on Foreign Language Anxiety (FLA) among university students (Indonesia and English study Programs). Using a qualitative phenomenological approach, data were collected from 300 students across multiple institutions in the Jabodetabek region. The study examines how AI tools, such as chatbots and adaptive learning platforms, influence students' anxiety levels during foreign language learning. Key findings indicate that AI reduces FLA by providing personalized learning experiences, real-time feedback, and low-pressure environments for language practice. However, some students reported increased anxiety due to the perceived constant monitoring and the lack of human interaction. The study concludes that while AI offers significant benefits in reducing anxiety, it also introduces new forms of stress, particularly related to technological engagement. This paper contributes to the existing literature by addressing the emotional dimensions of AI integration in language education, providing insights for educators on how to balance AI tools with human interaction to maximize the learning experience. Future research should focus on developing AI tools that integrate emotional support alongside cognitive feedback to further mitigate FLA.